Children and Adolescents With SARS-CoV-2 Infection: Epidemiology, Clinical Course and Viral Loads. Issue 12 (December 2020) - Maltezou, Helena C.; Magaziotou, Ioanna; Dedoukou, Xanthi; Eleftheriou, Eirini; Raftopoulos, Vasilios; Michos, Athanasios; Lourida, Athanasia; Panopoulou, Maria; Stamoulis, Konstantinos; Papaevangelou, Vasiliki; Petinaki, Efthimia; Mentis, Andreas; et al.
Abstract : Background: There is limited information on severe acute respiratory syndrome virus 2 (SARS-CoV-2) infection in children. Methods: We retrieved data from the national database on SARS-CoV-2 infections. We studied in-family transmission. The level of viral load was categorized as high, moderate, or low based on the cycle threshold values. Results: We studied 203 SARS-CoV-2-infected children (median age: 11 years; range: 6 days to 18.4 years); 111 (54.7%) had an asymptomatic infection. Among the 92 children (45.3%) with coronavirus disease 2019 (COVID-19), 24 (26.1%) were hospitalized. Infants <1 year were more likely to develop COVID-19 (19.5% of all COVID-19 cases) ( P -value = 0.001). There was no significant difference between viral load and age, sex, underlying condition, fever and hospitalization, as well as between type of SARS-CoV-2 infection and age, sex, underlying condition and viral load. Transmission from a household member accounted for 132 of 178 (74.2%) children for whom the source of infection was identified. An adult member with COVID-19 was the first case in 125 (66.8%) family clusters. Child-to-adult transmission was found in one occasion only. Conclusions: SARS-CoV-2 infection is mainly asymptomatic or mild during childhood. Adults appear to play a key role in spread of the virus in families. Most children have moderate or high viral loads regardless of age, symptoms or severity of infection. Further studies are needed to elucidate the role of children in the ongoing pandemic and particularly in light of schools reopening and the need to prioritize groups for vaccination, when COVID-19 vaccines will be available.